The Notes Procedures of Translating Islamic Terms in I Am Malala Novel - Danti Pudjiati; Ernawati Ernawati (Buletin Al-Turas, 2016)
AbstractThe writers focus on the analysis of notes procedures, that is, the translation procedure in translating Islamic terms in I Am Malala novel published in 2014and translated by Ingrid Dwijani Nimpoeno. They described notes procedures applied by Indonesian translator to translate the terms. They applied descriptive qualitative method to analyze the data based on Newmark’s procedure of notes. Besides, they utilize the mono lingual and bilingual dictionaries to support the analysis of the meaning in source and target language.The terms are divided into two categories: terms as knowledge and as worship. This reveals that nine terms translated by using notes within the text (one notes as an alternative to translated word, one notes as a participial group, one notes as an adjectival clause, one notes in brackets, two notes as a noun in apposition, three notes in parentheses);  one term translated by using notes within the text (as an adjectival clause)  and notes or glossary at the end of book; and third, one term translated by using notes at bottom of page (footnote) and notes or glossary at the end of book. In other words, the procedure of notes within the text is the most dominant---Abstract Penulis fokus pada analisis mengenai prosedur pemberian catatan/keterangan terkait penerjemahan istilah-istilah keislaman dalam novel I Am Malala yang terbit tahun 2014 yang diterjemahkan oleh Inggrid Dwijani Nimpoeno. Kajian ini akan menggambarkan prosedur yang digunakan oleh penerjermah Indonesia dalam menerjemahkan istilah keislaman. Metode yang digunakan dalam analisis pada tulisan ini adalah metode kualitatif deskriptif yang mengacu pada prosedur Newmark. Selain iut, juga digunakan kamus satu dan dwi bahasa untuk mendukung analisis penerjemahan dalam bahasa sumber dan bahasa sasaran. Istilah keislaman dibagi dua kategori, yaitu istilah ilmu pengetahuan dan istilah ritual. Kajian ini menunjukkan bahwa ada sembilan terjemahan istilah yang diberi catatan dalam teks (satu catatan sebagai terjemahan alternatif, satu catatan sebagai kelompok bagian, satu catatan sebagai klausa ajektif, satu catatan dalam kurung, satu catatan sebagai kata benda oposisi, tiga catatan dalam dua garis kata sisipan); satu terjemahan istilah menggunkan catatan dalam teks sebagai klausa ajektif, dan terdapat catatan atau glosari di akhir buku. Ketiga, satu terjemahan istilah menggunakan catatan kaki dan catatan atau glosari di akhir buku. Dengan kata lain, prosedur pemberian catatan yang dominan adalah di dalam teks.